2012
DOI: 10.5603/cj.2012.0106
|View full text |Cite
|
Sign up to set email alerts
|

Hoarseness subsequent to cardiovascular surgery, intervention, maneuver and endotracheal intubation: The so-called iatrogenic Ortner’s (cardiovocal) syndrome

Abstract: Background:The clinical characteristics and outcomes of hoarseness subsequent to cardiovascular surgery, intervention, maneuver and endotracheal intubation have not been systematically elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…A systematic review of hoarseness after thoracic cardiovascular surgery, which included newborn and paediatric patients, suggested that the rate of persistent hoarseness was 33%. 14 In our study, the overall rates of partial recovery and persistent VCP were 34.4 and 21.8%, respectively. Overall, only 43.8% of the patients had full recovery after follow-up at 1 year.…”
Section: Discussionmentioning
confidence: 43%
“…A systematic review of hoarseness after thoracic cardiovascular surgery, which included newborn and paediatric patients, suggested that the rate of persistent hoarseness was 33%. 14 In our study, the overall rates of partial recovery and persistent VCP were 34.4 and 21.8%, respectively. Overall, only 43.8% of the patients had full recovery after follow-up at 1 year.…”
Section: Discussionmentioning
confidence: 43%
“…Mann-Whitney U test or independent sample t test was used between two groups, and analysis of variance was used to assess the significance of differences among 3 groups as appropriate. We enrolled patients scheduled for cardiac surgery due to the lengthy intubation involved during surgery and during monitoring in intensive care [10][11][12]. We observed correlation between total length of intubation and effects in laryngopharyngeal structures.…”
Section: Discussionmentioning
confidence: 99%
“…The left RLN is more prone to injury by compression or traction because of its lengthy course, especially around the aortic arch and also its close relationship with major blood vessels in the mediastinum. The association of left RLN paralysis with a cardiovascular pathology was termed as cardiovocal syndrome (5,6,11,12). It was first described in a series of three cases of mitral stenosis suffering from hoarseness by Ortner in 1897 (5).…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in a series of three cases of mitral stenosis suffering from hoarseness by Ortner in 1897 (5). A wide variety of diseases, including congenital or adult cardiac conditions (such as mitral valve disorders, aneurysms of aorta and pulmonary artery, pulmonary hypertension, and tumors of left atrium and ventricles) and iatrogenic conditions (such as cardiovascular surgery and cardiac interventions) can result in hoarseness through RLN paralysis by either compressing or stretching effects (6,11,12). It was hypothesized that palsy results from compression of the left RLN between the pulmonary artery and either the aorta or aortic ligament due to cardiopulmonary pathology (6).…”
Section: Discussionmentioning
confidence: 99%